PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN ( Studi Kasus Perawat RSUD Bangkinang ) - Sri Mailinda; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Human resources have great control in a company. To determine whether a company is progressing or not, it depends on the quality and quantity of its human resources. This research uses explanatory research with a quantitative approach. There are two independent variables used in this study, namely training as (X1) with indicators namely training content, training methods, instructor attitudes and skills, length of time training and training facilities. Work environment as (X2) with indicators of physical work environment and non-physical work environment. While the dependent variable in this study is employee performance (Y) which consists of indicators of quality of work results, quantity of work results and timeliness. This study resulted in a positive and significant influence between training and work environment on employee performance with F count 13,201> F table 3,162 as well as partial test or t test for the training variable (X1) obtained t count 4.720> from t table 1.672 with a significance value <0.05. Shows that training has an effect on employee performance. For the work environment variable (X2) it is obtained in the t table 3,220> t table 1,672 with a significance value <0.05. This test shows the influence of the work environment on employee performance. Keyword : Human Resourch, Training, Wor Environmant